Assessment of the Efficiency of Combined Seeding Rates of Common Vetch and Ryegrass for Controlling Weed Development in Organic Forage Cultivation Systems - Hüseyin Çağlar; Serap Kizil Aydemir; Koray Kaçan (Life)
Weed suppression is a crucial factor in sustainable agriculture, and optimizing plant mixtures can enhance weed control efficiency. This study evaluates the effects of different mixture ratios of common vetch (Vicia sativa L.) and annual ryegrass (Lolium multiflorum L.) on forage yield, biomass production, dry matter production, and weed suppression in organic forage cropping systems. Field experiments were conducted during the 2021–2022 growing season at two locations in Turkey: Ankara/Yenikent and Manisa/Beydere, using 11 mixture ratios ranging from 100% vetch to 100% ryegrass. Results showed that ryegrass-dominant mixtures, particularly 10% vetch/90% ryegrass and 30% vetch/70% ryegrass, achieved the highest forage and dry matter yields while maintaining effective weed suppression. Pure ryegrass systems (100% ryegrass) exhibited the highest overall productivity, whereas pure vetch (100% vetch) treatments were less effective in weed control and biomass production. Environmental differences between locations significantly influenced the performance of mixtures, with Manisa/Beydere yielding higher overall results. This study highlights the potential of optimizing vetch–ryegrass mixtures to balance forage yield, weed suppression, and adaptability in organic cropping systems, offering practical insights for sustainable forage production. Ryegrass-dominated mixtures (30% V 70% RG, 60% V 40% RG) have been shown to provide high yields, effective weed suppression, and better nutritional benefits than vetch.